GLOBAL FINANCIAL CRISIS: AN ISLAMIC MANAGEMENT APPROACH - Santoso, Ivan Rahmat; Olilingo, Fahruddin Zain (International Journal of Islamic Business & Management, 2021)
The purpose of this study is to determine the solutions to financial crises based on the perspective of Islamic management. It also discusses the roles of faith and Islamic monotheism in managing the global financial crisis. The qualitative method was used to obtain data from books and articles related to Islamic management based on Qur’an and Hadith. These data were further analyzed and used as a solution to problems related to the global financial crisis by Islamic values. The result showed that the values of faith and monotheism following organizational policy and management tend to minimize financial speculative actions and greed. In addition, these values assist managers in planning, organizing, directing, and supervising their subordinates under Islamic rules and regulations. The application of this value is mainly reflected in the aspects of behavior, organizational aspects, and system aspects through the mechanism of placing the sharia supervisory board and profit-sharing in Islamic financial institutions, simplicity, and avoiding is in organizational management as well as the principle of prudence and avoiding speculative action. This research supports the role of the Islamic management system in winning finances and implementing organizational policies to overcome global financial problems.JELClassification Codes: G01, H12, D46.